Planning, development, monitoring and evaluation of the Academia da Cidade do Recife action plan during COVID-19 - Danyelle de Cássia Ribeiro de Oliveira; Tatiana Martins Ferraz Holmes; Emmanuelly Correia de Lemos; Rafael Miranda Tassitano; Raquel Bezerra Pajeú; Gledson da Silva Oliveira; Luiz Eduardo Nunes de Souza; Renan Wallacy Yvson dos Santos; Charles Barbosa Gomes da Silva; Marcílio Paulo da Silva; Gabriela Maranhão Câmara Campos; Ricardo Augusto Menezes da Silva (Revista Brasileira de Atividade Física e Saúde)
The aim of the study was to describe the Programa Academia da Cidade do Recife (PAC-REC) action plan during the social isolation requirement due to the COVID-19 pandemic. As temporary measures to confront the COVID-19, the City of Recife has published a contingency  plan, which suspended the non-essential services, including the presential operations of PAC-REC. Considering the program's commitment to the Unified Health System and to the Primary Health Care the PAC's board committee developed an action plan, restructuring its potential through the reorganization of remote activities to be offered to their users. The action plan has six stages encompassing planning (first and second), development (third and fourth), monitoring and evaluation (fifth and sixth). Despite the changes in the epidemiological scenario and the format of actions, the PAC-REC is maintaining its Health Promotion actions throughout its territory.